Role of Social Empowerment in Sustainable Development: A Sociological Study based on Selected Villages in Karaveddy Divisional Secretariat Division, Jaffna - Rajeskannan, R. (JUICE- 2012 University of Jaffna, 2012)
This research is trying to sociologically elaborate the contributions and the contradictions between the process of social empowerment and the sustainable rural development. And also it will provide the guidelines to promote the processes of rural social empowerment to achieve the target of sustainability. This research should understand the dimensions of empowerment which are implementing in these research areas, practical contributions of community empowerment in sustainable development in grass root level. The important orientations and strategies to promote social empowerment process to attain the sustainability and the opportunity to enhance the attitude base, self administration base and economic base for sustainable development. It should stress the importance of attitudinal criteria of the people such as sense of solidarity, democratic values, spirit of co-operation, collective spirit, creative spirit and spirit of self-reliance as alternatives for effective empowerment for sustainable development. It should recommend the new orientations for the effective empowerment strategies for sustainable rural development.
Keywords: Empowerment; Sustainable Development; Marginalization; Self Administration